Pemodelan Perubahan Tata Guna Lahan dan Koefisien Limpasan Dengan Metode Pembelajaran Terawasi Pada DAS Cisadane - Maulana, Aryo Setyo; Hidayat, Dina P.A (SAINSTEK, 2024)
The river is one of the main sources to meet human water needs, besides that the river is also used as the main irrigation for irrigation, one of which is the Cisadane river. On the other hand, population growth is increasing every year, forcing people to look for land to build a place to live. With the river as a source of water and livelihood, people build residential land around the river. This has led to changes in land use around the river, causing the effectiveness of the river as a place to collect rainwater to be affected. The purpose of this research is to find out how far the impact of land use change is for the Cisadane River Watershed. In this study the authors used medium satellite imagery, namely Landsat Satellite Imagery. The method used is the Supervised Classification method. Land use modeling is carried out with a span of 10 years, by taking one year as training data, with land use modeling then obtained the value of Coefficient C. Furthermore, another Coefficient C value is obtained from calculations using discharge data, rainfall intensity, and land area. The 2 C values are then compared whether the previously obtained data is appropriate or not.